Distribution of the root system of peach palm under drip irrigation - Lopes, Adriano Da Silva; Hernandez, Fernando Braz Tangerino [UNESP]; Alves Júnior, José; Oliveira, Gabriel Queiroz De (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
The incorporation of technologies has resulted in increased productivity and the more rational management of peach palm, with irrigation being an important tool for certain regions. Thus, studies leading to proper crop management are extremely important, such as the estimate of the effective depth of the root system, which is indispensable for proper irrigation management. The objective of this study was to evaluate the effects of different irrigation depths, as applied by drip irrigation, on the distribution of the root system of peach palm. This experiment was conducted in Ilha Solteira, São Paulo State, Brazil, with drip irrigation, with the two systems (flow of 0.0023 m³ h-1) consisting of four irrigation treatments corresponding to 0, 50, 100 and 150% of Class 'A' pan evaporation. After five years, an analysis of the Bactris gasipaes root system was performed at a distance of 0.0, 0.5 and 1.0 meters from the trunk, collecting sampling at two depths (0.0 to 0.3 m and 0.3 to 0.6 m) via the auger method (volumetric analysis). We concluded that the effective depth of the root system used for irrigation management should be a maximum of 0.3 meters.

A incorporação de tecnologias vem trazendo aumento de produtividade e manejo mais racional da pupunheira, sendo a irrigação uma ferramenta importante para algumas regiões produtoras. Nesse sentido, estudos que levem ao manejo adequado da cultura são de extrema importância, como a estimativa da profundidade efetiva do sistema radicular da cultura, indispensável para o correto manejo de irrigação. O objetivo deste trabalho foi avaliar os efeitos de diferentes lâminas de irrigação, aplicadas por gotejamento, sobre a distribuição do sistema radicular da pupunheira. Este experimento foi conduzido em Ilha Solteira, Estado de São Paulo, com irrigação por gotejamento, com dois gotejadores autocompensantes de 0,0023 m³ h-1 por planta, constando de quatro tratamentos de irrigação que corresponderam a 0, 50, 100 e 150% da evaporação da água do tanque Classe 'A'. Após cinco anos, foi realizada a análise do sistema radicular das pupunheiras, à distância de 0,0; 0,5 e 1,0 metro do estipe, com amostragens em duas profundidades, de 0,0 a 0,3 m e 0,3 a 0,6 m, pelo método do trado (análise volumétrica), concluindo-se que a profundidade efetiva do sistema radicular da pupunheira, utilizada para o manejo da irrigação, deve ser de, no máximo, 0,3 metro.
Distribuição do sistema radicular da pupunheira irrigada por gotejamento
Keywords: Bactris gasipaes; Raiz; Irrigação localizada; Manejo da irrigação; Bactris gasipaes; Roots; Localized irrigation; Irrigation management